Researching Acquisition Sequences: Idealization and De‐idealization in SLA. Issue 1 (20th January 2015) - Ellis, Rod; Hulstijn, Jan H.; Ellis, Rod; Eskildsen, Søren W.
<x xml:space="preserve">Abstract</x> Idealization plays a fundamental role in scientific inquiry. This article examines the case for maintaining the claim that the second language acquisition (SLA) of grammatical structures such as negation manifests identifiable stages of acquisition. It proposes that, while research has demonstrated the need for de‐idealization, there is no need to abandon the idealization itself. Drawing on work on idealization in the philosophy of science, it argues that the sequence of acquisition should be seen as a minimal idealization that is of continuing value for the domains of both SLA and, in particular, teacher education. This thesis is explored by examining four studies of second language negation that investigated the same data set. These studies afford important insights about the variability evident in the different stages and, as such, identify the limitations of the idealization but do not justify its rejection. The article concludes with a discussion of other factors (e.g., the first language and the role of instruction), the investigation of which may reveal further limitations and thus contribute further to the de‐idealization of the fundamental claim.